PERBANDINGAN PENERAPAN HUKUM PERJANJIAN TERTUTUP OLEH KPPU DAN JFTC: Comparison of the Application of the Law of Exclusive Dealing on Discout by KPPU and JFTC 025 - Putri, Bunga Amelia; Purnamasari, Dian (AMICUS CURIAE, 2025)
Agreements among business actors are common in the context of competition law in Indonesia and Japan. However, such agreements may be considered violations if they restrict competitors in the market, such as exclusive dealing on pricing or discounts. This study aims to describe the similarities and differences in the enforcement of laws by the Indonesia Competition Commission (KPPU) and the Japan Fair Trade Commission (JFTC). The research adopts a normative legal method with a comparative approach, utilizing secondary data and descriptive-analytical analysis. The findings reveal similarities in violations governed by Article 15(3)(b) of Indonesian Law No. 5 of 1999 and Article 19(6)(d) of Japan's Antimonopoly Act (AMA), such as the annulment of agreements and orders to cease unlawful practices. Differences are observed in the form of legal decisions, enforcement approaches, and the implementation of legal training programs in Japan. Additionally, while both KPPU and JFTC are independent authorities with similar mandates, JFTC holds the authority to enter business premises, which KPPU lacks. This study offers insights into the implementation of competition law regulations in the two countries.